A Multipath Routing Approach for Secure and Reliable Data Delivery in Wireless Sensor Networks. (11th March 2013) - Alwan, Hind; Agarwal, Anjali
Abstract : The severe resource constraints and challenging deployment environments of wireless sensor networks (WSNs) pose challenges for the security and reliability of data transmission for these networks. In this paper, we present and evaluate a secure and reliable routing mechanism offering different levels of security in an energy-efficient way for WSNs. Our approach uses node-disjoint routing and the selection mechanism of these paths depends on different application requirements in terms of security. The original data message is split into packets that are coded using Reed-Solomon (RS) codes and, to provide diverse levels of security, different number of fragments is encrypted related to the requested security level before being transmitted along independent node-disjoint paths. This technique makes encryption feasible for energy-constrained and delay-sensitive applications while still maintaining a robust security protection. We describe how to find the secure multipath, the number of these paths, and how to allocate fragments on each path seeking to enhance security and improve data reliability. Extensive analysis and performance evaluation show that data transmission security and reliability can be enhanced while respecting the resource constraints of WSNs.